Peran Agroforestry Terhadap Sosial Ekonomi Masyarakat Di Kereng Bangkirai Kota Palangka Raya: The Role of Agroforestry in Socio-Economy Communities in Kereng Bangkirai Palangka Raya City - Manurung, Polman; Yanarita, Yanarita; Tanduh, Yusintha; Octavianus, Robby (HUTAN TROPIKA, 2023)
This study aims to analyze te level of income of respondent and to analyze the level of income of respondent with the agroforestry system in the village of Kereng Bangkirai, Palangka Raya City. This study used a survey method with data collection including primary data and secondary data. The data analysis used in this research is income analysis, analysis in the contribution of agrosforestry income to total income to total income. This research was conducted in Kereng Bangkirai Village, Sabangau District, Palangka Raya City, Sarting from October to December 2020. These results showed that the income of respondents in Kereng Bangkirai Village using the agroforestry system was Rp.538.985.000, -/year. The level of contribution of agroforestry shows that the spearman correlation value (rho) of 0,82 means that the contribution of agroforestry activities to the respondent is very good.